Anatomical evaluation of the medial lingual foramen using cone-beam computed tomography: a retrospective study - Márcia Ingrid de CARVALHO; Tânia Mara Pimenta AMARAL; Cláudia Borges BRASILEIRO; Lucas Guimarães ABREU; Evandro Neves ABDO (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: To evaluate the frequency of medial lingual foramina present in the cortex of the mandible using cone beam computed tomography (CBCT). Methods: A total of 953 CBTC exams of the mandible were evaluated to determine the presence of canals in the mandibular midline, canal location in relation to the mental spine, canal diameter, distance to the base and alveolar crest of the mandible, trajectory of the canal, and coincidence measurements of the panoramic image containing the location of the canal in relation to the mental spine. Results: Foramina were located in three positions: above the mental spine (FSS) 89.2%, below the mental spine (FIS) 67.9%, and other positions (FOP) 21.3%. Non-edentulous individuals had a significantly higher number of FSS than did edentulous individuals (P<0.001). Male individuals presented a significantly greater distance from the FSS (P=0.001), FIS (P=0.045) and FOP (p=0.002) to the base of the mandible than female individuals. Younger individuals presented a significantly higher distance from the FSS (P=0.001) and FIS (P=0.001) to the alveolar crest of the mandible. Male individuals had a significantly greater FIS (P=0.002) and FOP (P=0.001) diameter than female individuals. Male individuals had a significantly higher number of bifurcations in FOP than female individuals (P=0.017). Conclusion: CBCT supplies the provider with a detailed assessment of the foramina and canals, which improves the quality of surgical planning and mitigates the chances of surgical intercurrences.